Implications of Tourism Industry Competitiveness on Culinary Industry Revenue and Digital Transactions in ASEAN Countries - Fransiskus Handoko; Heru Subiyantoro; Pudji Astuty (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The tourism industry serves as a key economic driver across ASEAN countries, yet its broader economic implications beyond direct sectoral contributions remain underexplored. As the region continues its post-pandemic recovery from 2019 to 2024, understanding how tourism competitiveness stimulates related sectors such as the culinary industry and digital economy has become increasingly important for integrated development strategies. This study aims to analyze the implications of tourism industry competitiveness on culinary industry revenue and digital transactions in ASEAN countries. The research employs a quantitative approach using panel data regression analysis. The sample covers 10 ASEAN member countries observed annually from 2019 to 2024, with data sourced from the World Economic Forum's Travel & Tourism Development Index (TTDI), international organizations, and national statistical agencies. The results of the panel data regression indicate that tourism industry competitiveness has a significant and positive effect on both culinary industry revenue and digital transactions across ASEAN countries. These findings suggest that enhanced tourism competitiveness reflected in improved infrastructure, effective policies, and favorable business conditions generates substantial spillover effects that benefit the culinary sector through increased tourist spending on local cuisine, while simultaneously accelerating digital transaction adoption as tourists increasingly utilize online booking platforms, cashless payments, and digital services throughout their travel experiences. The study underscores the strategic role of tourism competitiveness as a catalyst for broader economic transformation, highlighting the importance of integrated policies that leverage tourism growth to strengthen related industries and accelerate digitalization across the ASEAN region.